OʻZBEKISTONDA AGROTURIZMNI RIVOJLANTIRISH IMKONIYATLARI - Mirzokulova Kumush Mirshakarovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2023)
The article examines objects that can receive tourists in the field of agrotourism, and a list is formed based on them. It should be noted that the official pages of tourism and social networks provide detailed information about agrotourism facilities for the development of programs for tour operators and independent visits by tourists.